Enhancement of Superconducting Critical Temperature in Bi(Pb)-Sr-Ca-Cu-O System by Li-doping - Nguyen, Khac Man (Old Journal, 2019)
We have studied the superconducting transition of the high-Tₛ Li-doped Bi(Pb)-Sr-Ca-Cu-O superconductors by the DC-resistivity and AC-susceptibility measurements. It was found that Li⁺ cations are partially substituted for Cu²⁺ ions. Doping hole by Lithium substitution was supposed to take place in both OP and IP CuO₂ planes. Consequently, the hole concentration increases in the CuO₂ planes. The onset temperature of superconducting transition, Tₒₙₛₑₜ was observed to increase with Li-doping content as well as the sintering time at 850°C. We suppose that the optimum hole doping was obtained at 5% Li-doping and the sintering period of 20 days (S05B) with the value of Tₒₙₛₑₜ up to 116 K.